Assessment of safety characteristics, postbiotic potential, and technological stress response of Leuconostoc strains from different origins for their use in the production of functional dairy foods. (1st August 2022) - Ramos, Inés María; Rodríguez-Sánchez, Sara; Seseña, Susana; Palop, María Llanos; Poveda, Justa María
Abstract: Fifty-two Leuconostoc strains isolated from artisanal Manchego cheese and craft beer were analysed for some safety traits, postbiotic potential, α-glucosidase inhibitory activity, and response against technological stress conditions. Twelve of the strains produced biogenic amine concentrations higher than 200 mg/L and were discarded. All the strains except for three were susceptible to streptomycin, clindamycin, erythromycin, and chloramphenicol, and the results for ampicillin and tetracycline varied with both the species and the strains. None of the strains were β-haemolytic nor showed DNAse, coagulase, lipase, or gelatinase activities. Concentrations of γ-amino butyric acid, ornithine and tryptophan varied with the strains and with the medium of growth, reaching values up to 603.42, 251.00, and 1020.08 mg/L, respectively. Lactic acid was the most produced organic acid followed by acetic and propionic acids. The α-glucosidase inhibitory activity was an intraspecific property (maximum value of 49.16%). Overall, strains C2, C4, C5, C8, B4, B9, and B15 showed the best results and could be considered potential candidates for use in functional dairy products. Among them, those from artisanal Manchego cheese had a better response against technological stress factors. This is the first study to report the production of postbiotic compounds by Leuconostoc strains in sheep's milk. Graphical abstract: Image 1 Highlights: Fifty-two Leuconostoc strains from artisanal cheese and craft beer were assayed. None were β-haemolytic nor showed DNAse, coagulase, lipase, or gelatinase activities. GABA, Orn, and Trp reached values up to 603.42, 251.00 and 1020.08 mg/L, respectively. In addition to lactic, the strains produced acetic and propionic acids and acetoine Four strains from Manchego cheese and 3 from craft beer showed the best results.